PERAN PERPUSTAKAAN GAMPONG LAMDINGIN DALAM MENINGKATKAN MINAT BACA SANTRI TPA (TAMAN PENDIDIKAN AL-QUR’AN) - Sri Wahyuni (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2023)
Since the implementation of Regional Autonomy, the term village can be referred to by other names, for example in West Sumatra Province it is known as "Nagari" and in Aceh Province it is known as "Gampong". Currently, the development of the gampong/village library is certainly not just a structural complement to the gampong/kelurahan government, but it is a basic thing that must be fulfilled to add references and inspiration in changing people's mindsets that have an impact on a prosperous life. In this study, the researcher used a qualitative descriptive type of research. In retrieving data the author uses the Snowball Sampling Technique. Data collection techniques through observation, interviews and documentation. The data analysis technique starts from data reduction, data presentation and conclusion drawing. Guarantee the validity of the data in this study using triangulation of sources. The results of the study indicate that the role of the Gampong Lamdingin Library in increasing students' reading interest includes (a). Book review activities that are held regularly, (b) Cooperation with mobile libraries, (c). Coloring activities to increase students' creativity, (d). Require the students before starting the recitation to visit the library and read at least 20 minutes. With activities like this, it is hoped that the village library will make a major contribution to the development of reading interest for students and synergize with the role of the family, the environment, and the surrounding community